The dynamic consultation : a discourse analytical study of doctor-patient communication - Cordella, Marisa (Pragmatics & beyond ;, 2004)
This book introduces a unique model of medical discourse that identifies the forms of talk - voices - that doctors and patients use during the consultation, and studies the dynamic interaction as it unfolds particularly in follow-up visits. Natural recordings, semi-structured interviews, questionnaires and ethnographic observations provide the data for the research, which was carried out in an Outpatient Clinic in Santiago, Chile. Using an interactional sociolinguistic approach, analysis of the data identifies doctor-patient communication as a micro-performance of broader socio-cultural realit.